PENGARUH MOTIVASI DENGAN KEMANDIRIAN BELAJAR SISWA SMK 2 NURHASANAH MEDAN DALAM PEMBELAJARAN DARING - Suci Anggira; Samsul Bahri; Ahmad Laut Hasibuan; Rahmat Kartolo (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2022)
Online learning is learning that limits teachers and students to interact in conveying knowledge. The limitations of this interaction cause various kinds of obstacles in the implementation of learning. One of them is the low independence of student learning caused by the limited time to study, making it difficult for teachers to meet learning outcomes. Therefore, the purpose of this study was to determine whether there is an influence of learning motivation on student learning independence. The method used in this research is descriptive qualitative to provide whether or not there is an influence between motivation and student learning independence. The research was conducted at SMK 2 Nurhasanah Medan with a sample of 30 people. The instrument used is a questionnaire with 20 statements each. The analysis used is univariate analysis and chi square test. The results showed that there was an influence between motivation on student learning independence.